2015
DOI: 10.1021/ic502637q
|View full text |Cite
|
Sign up to set email alerts
|

Magic-Size II–VI Nanoclusters as Synthons for Flat Colloidal Nanocrystals

Abstract: Five new, discretely sized, magic-size II–VI nanoclusters are synthesized in primary-amine bilayer templates and are isolated as the derivatives [(CdS)34(n-butylamine)18], [(ZnS)34(n-butylamine)34], [(ZnSe)13(n-butylamine)13], [(CdTe)13(n-propylamine)13], and [(ZnTe)13(n-butylamine)13]. The nanoclusters are characterized by elemental analysis, UV–visible absorption spectroscopy, laser-desorption-ionization mass spectrometry, and transmission electron microscopy. Four of the nanocluster precursors are converted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
222
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(243 citation statements)
references
References 54 publications
16
222
3
Order By: Relevance
“…These precisely defined clusters can be achieved with different materials leading either to quantum platelets 120 or to quantum nanowires such as ZnTe. 129 These quantum wires exhibit similar optical properties as quantum platelets with well defined absorption peaks and unusually thin transitions.…”
Section: Ligand Templatingmentioning
confidence: 99%
“…These precisely defined clusters can be achieved with different materials leading either to quantum platelets 120 or to quantum nanowires such as ZnTe. 129 These quantum wires exhibit similar optical properties as quantum platelets with well defined absorption peaks and unusually thin transitions.…”
Section: Ligand Templatingmentioning
confidence: 99%
“…Their binding strengths are much weaker and they can be easily washed away during purification [65, 66]. While cadmium-rich QDs are typical whenever X-type ligands are used, minimizing the concentration of these ligands and including excess L-type ligands can yield a Cd:Se stoichiometry near 1:1, indicating the dominance of neutral facets on the surface [67-70]. It is also possible to prepare anion-rich QDs [71], which require an excess of Z-type ligands such as phosphines for stabilization.…”
Section: Quantum Dot Ligand Coordinationmentioning
confidence: 99%
“…Interestingly, other magic-sized clusters have been reported that seem to be distinct, either synthesized with X-type ligands to yield cadmium-rich QDs [79], or synthesized with excess L-type amines to yield neutral QDs (e.g. Cd 33 Se 33 ) [69, 70]. However, these have not been crystallized to a level suitable for X-ray crystallography presumably due to the flexibility of alkyl chains on the ligands.…”
Section: Quantum Dot Ligand Coordinationmentioning
confidence: 99%
“…Another report by Buhro et al. demonstrated that ZnSe nanoplates can be prepared from (ZnSe) 13 (n‐butylamine) 13 nanoclusters . Other than the direct synthetic methods, cubic ZnSe and wurtzite ZnSe spherical nanoparticles as well as wurtzite ZnSe nanorods were synthesized via a sequential cation exchange method starting from cadmium‐containing nanoparticles …”
Section: Types Of Zn‐containing Semiconductor Ncsmentioning
confidence: 99%
“…In the aspect of ZnS nanoparticles with a 2D shape, Buhro et al. assembled magic‐sized nanoclusters into stacked ZnS nanoplatelets (Figure c) . Pradhan et al.…”
Section: Types Of Zn‐containing Semiconductor Ncsmentioning
confidence: 99%